Our Founders - article editotial (Литьë и металлургия, 2002)
Belarussian social association of founders and metallurgists ОАО “Minsk plant of heating equipping”  RUP “Rechitski hardware plant” ОАО  “Mogilev metallurgical works” ODO “Interfoundry”